Multi-Step Multi-Input One-Way Quantum Information Processing with Spatial and Temporal Modes of Light - Ukai, Ryuji (Springer, 2016)
In this thesis, the author develops for the first time an implementation methodology for arbitrary Gaussian operations using temporal-mode cluster states. The author also presents three experiments involving continuous-variable one-way quantum computations, where their non-classical nature is shown by observing entanglement at the outputs. The experimental basic structure of one-way quantum computation over two-mode input state is demonstrated by the controlled-Z gate and the optimum nonlocal gate experiments. Furthermore, the author proves that the operation can be controlled by the gain-tunable entangling gate experiment.